Technology in Education. Transforming Educational Practices with Technology : First International Conference, ICTE 2014, Hong Kong, China, July 2-4, 2014. Revised Selected Papers - Li, Kam Cheong; Wong, Tak-Lam.; Cheung, Simon K. S.; Lam, Jeanne; Ng, Kwan Keung; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the International Conference on Technology in Education, ICTE 2014, held in Hong Kong, in July 2014. The 18 revised full papers and 4 short papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections on application of mobile technologies in e-learning; technology advancement in e-learning systems; innovations in e-learning pedagogy; open education and institution e-learning policy.
Application of mobile technologies in e-learning -- Technology advancement in e-learning systems -- Innovations in e-learning pedagogy -- Open education and institution e-learning policy.
Keywords: Education; Social sciences -- Data processing; Computers and Education; Educational Technology; Computer Appl. in Social and Behavioral Sciences